2022
DOI: 10.1039/d1tb02601a
|View full text |Cite
|
Sign up to set email alerts
|

Self-assembled nanoparticles based on supramolecular-organic frameworks and temoporfin for an enhanced photodynamic therapy in vitro and in vivo

Abstract: Water-soluble three-dimensional supramolecular-organic frameworks (SOFs) and temoporfin (mTHPC) are discovered to form uniform self-assembly nanoparticles. These nanoparticles demonstrate an improved 1O2 generation efficiency due to a reduced aggregation-caused quenching effect....

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 40 publications
0
17
0
Order By: Relevance
“…31 When the tetrahedral backbone is incorporated with 2-aminoethoxy groups at the ends of the appended 4-phenylpyridinium units, the resulting precursor T2 co-assembles with CB[8] (1 : 2) to afford supramolecular organic framework SOF-OC 2 N which was revealed to have good biocompatibility and water-solubility. 31,35 We thus further introduced thiol groups on the four side chains to construct SOF-p1 and SOF-p2 as polymeric precursors for maleimide–thiol conjugation of AlDox (Scheme 1). For the preparation of SOF-p1 , four cysteine groups were first introduced to the tetrahedral backbone to afford compound T1 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…31 When the tetrahedral backbone is incorporated with 2-aminoethoxy groups at the ends of the appended 4-phenylpyridinium units, the resulting precursor T2 co-assembles with CB[8] (1 : 2) to afford supramolecular organic framework SOF-OC 2 N which was revealed to have good biocompatibility and water-solubility. 31,35 We thus further introduced thiol groups on the four side chains to construct SOF-p1 and SOF-p2 as polymeric precursors for maleimide–thiol conjugation of AlDox (Scheme 1). For the preparation of SOF-p1 , four cysteine groups were first introduced to the tetrahedral backbone to afford compound T1 .…”
Section: Resultsmentioning
confidence: 99%
“…31,32 Previously we found that SOFs can in situ load anticancer agents and overcome the multidrug resistance of tumour cells to realize intracellular drug delivery and efficacy enhancement through the EPR effect. [32][33][34][35] Because the tetrahedral components can be readily functionalized at the ends of the appended aromatic units, 36 we conjectured that SOFs might be developed as albumin surrogates to conjugate AlDox or other small-molecule anticancer agents to attain increased efficacy through efficient conjugation, intracellular delivery and stimuli-responsive release. Here we describe the preparation of two SOF-based prodrugs by attaching AlDox to the interior of their regular pores through the thiol-maleimide conjugation approach.…”
Section: Introductionmentioning
confidence: 99%
“…Temoporfin is a neutral porphyrin PDA clinically used in the treatment of skin cancers (Chart ). We recently found that dSOF1a , b , h could also include this PDA . Their inclusion efficiencies were very close, indicating that the inclusion was also driven by hydrophobicity.…”
Section: Sofs As In-situ Loading Carriers For Drug and Dna Deliverymentioning
confidence: 99%
“…The tetrahedral backbone can be modified by introducing different substituents to afford T1b-h , which coassembled with CB[8] to give rise to similar supramolecular architectures dSOF1b – h (Scheme ). ,, dSOF1g and dSOF1h formed by T1g or T1h displayed the highest water solubility of 8.0 mM, indicating that their hydrophilic groups could remarkably increase the water solubility of the frameworks. The maximum tolerated doses (MTDs) of Wistar rats for dSOF1a , dSOF1b , dSOF1g , and dSOF1h (three males and three females per group) were determined to be 17, 31, 49, and 77 mg/kg, respectively, which corresponded to values of 0.16, 0.30, 0.47, and 0.74 g for an adult of 60 kg weight by assuming a conversion coefficient of 6.25.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation